Cayman Islands : Assessment of the Supervision and Regulation of the Financial Sector-Volume II-Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews key findings of the detailed assessment of the Observance of Standards and Codes in the Financial Sector of the Cayman Islands. Banks in the Cayman Islands operate within a well-defined prudential regulatory framework, generally in accordance with Basel standards, that is, largely modeled after the framework currently in use in the United Kingdom. The two-tiered required minimum risk capital standards are significantly above those required by the Basel Capital Accord and are applied in practice based primarily on the perceived differences in risk related to bank ownership.